Microplastics in marine fishes of economic importance in Lima, Peru - Iannacone, José (2021)
The microplastics (PM) present in five fish species of economic importance in Peru were evaluated: Sciaena deliciosa (Tschudi, 1846) (Sciaenidae) “Lorna drum”, Isacia conceptionis (Cuvier, 1830) (Haemulidae) “Cabinza grunt”, Scartichthys gigas (Steindachner, 1876) (Blenniidae) "Giant blenny", Mugil cephalus (Linnaeus, 1758) (Mugilidae) "flathead grey mullet" and Scomber japonicus (Houttuyn, 1782) (Scombridae) "Chub mackerel". The stomach and gill contents of each fish were digested with 10% KOH, followed by a filtration process to search for PM. The MPs were classified by color and by shape. The contamination by PM found in the digestive tract of S. gigas presented higher values than those found in the other four species. No differences were observed in the amount of MP recorded in the gills between species. A positive correlation was only observed between the body length of I. conceptionis and MP of the digestive tract/fish, and between the weight of M. cephalus and MP of the digestive tract/fish. Blue, black and white were the dominant colours of MP in the digestive tract, and blue, black and fuchsia in gills. At the level of the digestive tract, the types of PM were fibre, fragments and film and in gills only fibres were found.